Exploring inequities in child welfare and child protection services: Explaining the 'inverse intervention law'. (October 2015) - Bywaters, Paul; Brady, Geraldine; Sparks, Tim; Bos, Elizabeth; Bunting, Lisa; Daniel, Brigid; Featherstone, Brid; Morris, Kate; Scourfield, Jonathan
Abstract: Attempts to record, understand and respond to variations in child welfare and protection reporting, service patterns and outcomes are international, numerous and longstanding. Reframing such variations as an issue of inequity between children and between families opens the way to a new approach to explaining the profound difference in intervention rates between and within countries and administrative districts. Recent accounts of variation have frequently been based on the idea that there is a binary division between bias and risk (or need). Here we propose seeing supply (bias) and demand (risk) factors as two aspects of a single system, both framed, in part, by social structures. A recent finding from a study of intervention rates in England, the 'inverse intervention law', is used to illustrate the complex ways in which a range of factors interact to produce intervention rates. In turn, this analysis raises profound moral, policy, practice and research questions about current child welfare and child protection services.